1998
DOI: 10.1021/bi982201+
|View full text |Cite
|
Sign up to set email alerts
|

Divalent Cations Stabilize Unstacked Conformations of DNA and RNA by Interacting with Base Π Systems

Abstract: Nucleic acid structure, stability, and reactivity are governed substantially by cations. We propose that magnesium and other biological inorganic ions unstack bases of DNA and RNA. This unstacking function of cations opposes their previously accepted role in stabilizing DNA and RNA duplexes and higher assemblies. We show that cations interact favorably with pi-systems of nucleic acid bases. These cation-pi interactions require access of cations or their first hydration shells to faces of nucleic acid bases. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
112
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(123 citation statements)
references
References 26 publications
8
112
2
Order By: Relevance
“…We also found that the existence of magnesium could significantly favor the nonhysteretic transition of endclosed DNA (Fig. 5), which is similar to our previous results that the existence of magnesium could favor the nonhysteretic transition on end-opened λ-DNA (10), likely due to the enhancement of the DNA base-pair stability by magnesium (25).…”
Section: Discussionsupporting
confidence: 91%
“…We also found that the existence of magnesium could significantly favor the nonhysteretic transition of endclosed DNA (Fig. 5), which is similar to our previous results that the existence of magnesium could favor the nonhysteretic transition on end-opened λ-DNA (10), likely due to the enhancement of the DNA base-pair stability by magnesium (25).…”
Section: Discussionsupporting
confidence: 91%
“…These results suggest that zinc could have an unstacking function in the adenine DNA glycosylase activity of gelonin. This would support the proposal by McFail-Isom et al (48) that cations have mechanistic roles in DNA bending, strand separation, DNA-protein recognition, base flipping, RNA folding, and catalysis through -interactions with the faces of DNA and RNA bases.…”
Section: Discussionsupporting
confidence: 88%
“…Williams and coworkers (32) reported a crystal structure of the d(CGCGAATTCGCG) duplex at 1.4 Å that was interpreted in terms of fractional occupancy of ions in the grooves of DNA. Subsequently, the ions Rb ϩ and Tl ϩ have been reported crystallographically in the spine of hydration at the ATT region (1,33,34), and Rb ϩ was located in the minor groove (35,36). The issue was revisited by Dickerson et al (37) in a high-resolution crystal structure determination that argued against ions in the minor groove, and the Williams group responded (38).…”
Section: Introductionmentioning
confidence: 99%